ANALISIS FATWA MUI TENTANG PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL - Marasabessy, Fachrul (Islamic Banking & Economic Law Studies (I-BEST), 2023)
Copyright is a type of intellectual property right, which has been widely discussed by the public lately. Based on data from the International Data Corporation (IDC), Indonesia in 2007 was listed in the top five countries with the highest levels of piracy and the biggest violators of Intellectual Property Rights. Indonesia is also known as one of the "paradise" for circulation of pirated and illegal goods. MUI as one of the Islamic religious institutions in the State of Indonesia has issued a fatwa regarding the protection of Intellectual Property Rights, which contains several considerations, legal basis, and the mafsada that arises.Departing from the problem above, there are several problems formulated to find out the background of the existence of the MUI Fatwa regarding the protection of Intellectual Property Rights, how the provisions of the MUI fatwa against IPR violations and how the implementation of the MUI Fatwa in the practice of photocopies of copyrighted books. While the data is obtained through documentation, observations and interviews which were then analyzed using descriptive qualitative methods, namely data in the form of spoken words or from people and their behavior that can be observed.The view of Islamic law regarding the provision of copyright protection is an appreciation for his efforts and sacrifices during the process of discovering intellectual works and these works can be included in the class of assets, namely intellectual property. With regard to the fatwa issued by the MUI regarding Copyright, the MUI views Copyright as one of the Huquq Maliyyah (property rights) that receives legal protection as mal (property) for the legal provisions issued by the MUI on Copyright. Copyright including property rights (milkiyah) in Islamic law can be obtained from various ways, including namely ihraz al-mubahat (free control of property), namely the method of ownership through control over assets that have not been controlled or owned by other parties so that assets that have become his property is obliged to be protected by both formal law and Islamic law as individual property rights. From the results of research in the practice of photocopying copyrighted book services "not violating" the rules set by the MUI, copying activities are only to make it easier for the public, especially students who need books for educational purposes. books copied (made) without asking permission from the creators.